The Effect of Quenching With Oil on Annealing Temperature Variations on The Hardness Of ST 37 Equivalent Steel - Muh Anhar; Yusuf Yusuf; Irianto SP; Ningrum Astriawati (Journal of Applied Engineering and Technological Science (JAETS), 2026)
ST37 equivalent steel is widely used in engineering applications due to its high ductility; however, its relatively low hardness limits its performance in wear-related components. This study investigates the effect of annealing temperature variations and different oil quenching media on the hardness of ST37 equivalent steel. Specimens were annealed at 750°C, 850°C, and 950°C with a holding time of 10 minutes, followed by quenching in three types of oil: SAE 15W-40 mineral oil, SAE 10W-40 semi-synthetic oil, and SAE 10W-40 fully synthetic oil. Hardness measurements were conducted using the Rockwell B scale (HRB) at five different points on each specimen. The results indicate a consistent increase in hardness with increasing annealing temperature for all quenching media. The highest hardness value, 43.4 HRB, was obtained at 950°C using fully synthetic oil, representing an improvement of approximately 4.58% compared to the untreated material. Among the tested media, fully synthetic oil exhibited the most effective cooling performance. These findings demonstrate that both annealing temperature and oil type significantly influence the hardness characteristics of ST37 equivalent steel.